1990
DOI: 10.2466/pr0.1990.66.2.623
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Character Styles of Vietnam Veterans with Posttraumatic Stress Disorder

Abstract: A total of 189 male Vietnam veterans who were admitted to a specialized inpatient treatment program were evaluated using the Millon Clinical Multiphasic Personality Inventory to assess character styles. The veterans were assessed for Posttraumatic Stress Disorder by using a subscale of the Minnesota Multiphasic Personality Inventory (MMPI) and 72% of the patients were classified as having Posttraumatic Stress Disorder. The character styles of passive-aggressive, schizoid, avoidant, and borderline were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…1) observed in our sample were consistent with findings from previous studies using DSM criteria. The studies cited earlier indicate high levels of DSM personality disturbance in the avoidant and passive aggressive categories (Hyer et al, 1991(Hyer et al, , 1994, schizoid, and borderline categories (Sherwood et al, 1990;Richman and Frueh, 1996), and in the antisocial category (Sierles et al, 1983;Keane and Wolfe, 1990). Social disregard, opportunism, impulsivity, tough-mindedness, and being quick tempered are consistent with "antisocial" personality disorder.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…1) observed in our sample were consistent with findings from previous studies using DSM criteria. The studies cited earlier indicate high levels of DSM personality disturbance in the avoidant and passive aggressive categories (Hyer et al, 1991(Hyer et al, , 1994, schizoid, and borderline categories (Sherwood et al, 1990;Richman and Frueh, 1996), and in the antisocial category (Sierles et al, 1983;Keane and Wolfe, 1990). Social disregard, opportunism, impulsivity, tough-mindedness, and being quick tempered are consistent with "antisocial" personality disorder.…”
Section: Discussionmentioning
confidence: 93%
“…Utilizing the Millon Clinical Multiaxial Inventory (MCMI), Hyer et al (1991Hyer et al ( , 1994 found high rates of avoidant and passive aggressive personality disorder. Sherwood et al, (1990), also using the MCMI, reported high rates of personality disorder in the schizoid, avoidant, passive aggressive, and borderline categories. Recent research by Richman and Frueh (1996) found that PTSD-diagnosed Vietnam veterans self-reported high levels of Cluster A symptomatology (paranoid, schizoid, and schizotypal), borderline symptomatology, and avoidant symptomatology when compared with outpatients with primary diagnoses of (1) anxiety disorders other than PTSD and (2) major depressive disorder.…”
Section: Combat-related Posttraumatic Stress Disorder (Ptsd)mentioning
confidence: 97%
See 1 more Smart Citation
“…Adults with personality disorder are more highly represented within PTSD cases in the US military (22,181,182), and a growing literature of fraudulent representations ofcombat exposure (183-187) may have tainted many veteran trauma studies. Exaggerations of symptoms (188) and misrepresentation of schooling (189) are found in PTSD.…”
Section: Personality Disordermentioning
confidence: 99%
“…When assessed by structured interview, combat veterans were found to have high rates of borderline, avoidant, and obsessive-compulsive personality disorders [8]. Studies using self-report measures found high rates of borderline, avoidant, passive-aggressive, antisocial, schizotypal, and schizoid personality disorders among combat veterans with PTSD [9][10][11]. There have been inconsistent associations reported between exposure to combat trauma and high incidence of antisocial personality disorder [12].…”
Section: Specific Traumas and Personality Disorder Profilesmentioning
confidence: 99%